Regulasi perpustakaan dan dilema penerapannya serta dampaknya pada masa depan profesi pustakawan - Pungki Purnomo (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2015)
As a unit or institution, the library can provide a meaningful contribution in building the intellectual community because that role can not be separated as a means of support for formal and informal education. Although today's decision-makers are beginning to pay attention to the problem of a library with many regulations set associated with the library. But unfortunately in practice some of the existing regulations through many dilemmas that consequently the role of school libraries in Indonesia is still facing various problems. This paper is as a review of some regulations libraries in reality on the ground causes a lot of dilemmas and matters that may lead to something that is not conducive to the development of libraries in the future, especially with regard to the librarian profession for graduates or bachelor of library science and information to make a career as the head of the school library. Because some library regulations made reality more favorable to the professional educators or teachers to fill the position of head of the library.